Clinical manifestations of Hepatitis B: its association with serum profile of cytokine genetic polymorphism - Campos, Mauricio de Souza; Schinonni, Maria Isabel; Freire, Songeli Menezes (Revista de Ciências Médicas e Biológicas, 2014)
Objective: This systematic review aims to review the correlation among the genetic polymorphism of cytokine, production and clinical presentation of these serum hepatitis B chronic. Methodology: For this we conducted a systematic review of articles obtained by searching the databases Journals Portal CAPES and Pub Med The papers selected were published between the years 200 and 2013. We used the following descriptors: 1. Chronic hepatitis B, 2. Cytokine gene polymorphism 3. Anti-hepatitis B / genetics, 4. Hepatitis B virus / genetics. Results: the articles found in the search, twenty-five (25), which were used in this review. Conclusion: The research on the correlation between the genetic polymorphism of cytokine production of these serum and clinical presentation of chronic hepatitis B is still incipient, although this may elucidate the immunological mechanisms responsible for viral clearance and the chronicity of the infection.